2015
DOI: 10.1371/journal.pone.0140283
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel Equi-Biaxial Stretcher for Live Cellular and Subcellular Imaging

Abstract: Cells in the body experience various mechanical stimuli that are often essential to proper cell function. In order to study the effects of mechanical stretch on cell function, several devices have been built to deliver cyclic stretch to cells; however, they are generally not practical for live cell imaging. We introduce a novel device that allows for live cell imaging, using either an upright or inverted microscope, during the delivery of cyclic stretch, which can vary in amplitude and frequency. The device de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The multi-well stretching system pictured in Figure 1 was built and calibrated based on previous designs (Arold et al, 2009;Imsirovic et al, 2015). Briefly, one or two 6-well plates with deformable elastic membranes are secured in the upper stage of the stretcher.…”
Section: Device Designmentioning
confidence: 99%
“…The multi-well stretching system pictured in Figure 1 was built and calibrated based on previous designs (Arold et al, 2009;Imsirovic et al, 2015). Briefly, one or two 6-well plates with deformable elastic membranes are secured in the upper stage of the stretcher.…”
Section: Device Designmentioning
confidence: 99%
“…Interestingly, the study also found direct evidence based on imaging that a global equibiaxial strain (17% strain applied to the elastic membrane on which cells were cultured) resulted in local stretching of the mitochondria with up to 32% linear strain. Furthermore, when lung fibroblasts were exposed to large transient equibiaxial stretches of up to 30%, mitochondria were seen to rupture ( Figure 3 ) at discrete locations immediately after the stretch [ 77 ]. To visualize mitochondria, cells were labeled with tetramethylrhodamine methyl ester (TMRM), a dye whose intensity is related to the inner mitochondrial membrane potential [ 78 ] and hence to ATP production [ 79 ].…”
Section: Mechanobiology Of Mitochondrial Structure and Functionmentioning
confidence: 99%
“…( B ) The top row shows the mitochondrial network of an entire cell imaged during constant strain application at increments of 0, 7, 14, and 30% change in membrane surface area. The bottom row shows the zoomed-in details of an individual cluster (green rectangle in top row) changing shape as higher strains are applied (green arrow), as well as a cluster undergoing fission and splitting into two smaller clusters (red arrow) [ 77 ].…”
Section: Figurementioning
confidence: 99%
“…A few studies focused on non-uniform strain fields using finite element modeling (FEM) 32 or experimental measurements 12 to quantify sample deformation. In most other cases, uniformity of the strain field in the region of the sample where cells are seeded was verified by FEM, 33 experimental measurements, 10,34,35 or both. 13,15,23,26 Although these studies provide detailed analysis of relevant sample deformation, characterization of local strain field and cell imaging are not carried out simultaneously.…”
Section: Introductionmentioning
confidence: 94%